2022
DOI: 10.1152/jn.00008.2021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that endpoint feedback facilitates intermanual transfer of visuomotor force learning by a cognitive strategy

Abstract: Humans continuously adapt their movement to a novel environment by recalibrating their sensorimotor system. Recent evidence, however, shows that explicit planning to compensate for external changes, i.e. a cognitive strategy, can also aid performance. If such a strategy is indeed planned in external space, it should improve performance in an effector independent manner. We tested this hypothesis by examining whether promoting a cognitive strategy during a visual-force adaptation task performed in one hand can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Intermanual transfer was facilitated in the endpoint feedback condition, suggesting that effector-independent learning was facilitated by a cognitive strategy [39]. Despite the differences of experimental design and tasks in the above-mentioned studies [17,[37][38][39][40], the cognitive aspect, which is inherent in the task, improved the intermanual transfer. It should be noted that our study design did not aim to elucidate the respective contributions of the cognitive and motor aspects to ipsilateral transfer.…”
Section: Plos Onementioning
confidence: 90%
See 3 more Smart Citations
“…Intermanual transfer was facilitated in the endpoint feedback condition, suggesting that effector-independent learning was facilitated by a cognitive strategy [39]. Despite the differences of experimental design and tasks in the above-mentioned studies [17,[37][38][39][40], the cognitive aspect, which is inherent in the task, improved the intermanual transfer. It should be noted that our study design did not aim to elucidate the respective contributions of the cognitive and motor aspects to ipsilateral transfer.…”
Section: Plos Onementioning
confidence: 90%
“…Explicit (cognitive) processes were found to be primarily responsible for intermanual transfer of a visuomotor adaptation task when participants adapted to a large visuomotor distortion of which they were aware [ 17 ]. Elements of the task environment, such as the type of visual feedback available, can also alter the balance between cognitive strategies and motor adaptation and affect intermanual transfer [ 39 ]. Intermanual transfer was facilitated in an endpoint feedback condition that consisted of cognitive strategy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We chose to only provide visual endpoint feedback to promote the role other intrinsic feedback mechanisms including proprioception during the trial. Furthermore, Havas et al (2021) have recently suggested that this can promote cognitive strategy use during motor learning compared to when feedback is presented continuously.…”
Section: Discussionmentioning
confidence: 99%